Profanity in songs. Seeking the limits of freedom of speech, and the reproduction and sanctioning of contemporary linguistic tendencies - Gajda, Krzysztof (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2018)
The article is showing the presence of vulgar expressions in song lyrics. This is a clear testimony to the changes in the customs and language of culture of recent decades. The paradox is that the development of negative phenomena can contribute to events naturally valued positively, such as expanding the sphere of freedom together with the birth of “Solidarity” or the abolition of the censorship institution with the transformation after 1989. Vulgarism today, after more than a quarter of a century since the release of language from the “care” of censorship, is intensively present in songs that many Poles find important. This stylistic device helps to express and shapes the expressed emotions, describe reality, and it is a manifestation of the generational fear of the sublime. The text discusses the songs of authors such as: Andrzej Garczarek, Jacek Kaczmarski, Kazik Staszewski, Krzysztof Grabowski (Grabaż), Marcin Świetlicki, Hubert Dobaczewski (Spięty), Paweł Sołtys (Pablopavo).